The Influence of Price & Product Quality on Purchase Decision through Brand Trust at Honda Gajah Mada Dealer Semarang: Honda Gajah Mada Dealer Semarang - ADE SATRIA NUGRAHA, ADE; Heri Prabowo; Prianka Ratri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to ascertain how brand trust influences buying decisions in relation to pricing and using purposive sampling technique with the criteria of residing in Semarang City and having purchased a Mobilio car from the Honda Gajah Mada dealer during the period of 2019 - 2023. This research uses a questionnaire and the SmartPLS 3.0 software. The study’s findings show that while price has no discernible positive influence on brand trust, product quality has a positive and significant impact on brand trust, and price has no positive influence on brand trust. When it comes to purchasing decisions, the relationship product quality. This research uses a quantitative methodology. The sample size used consists of 80 respondents, selected from customers of the Honda Gajah Mada Dealer in Semarang. The sample was obtained between price and product quality might be mediated by brand trust.